The Impacts of Petrochemical Activity and Climate Change on Polycyclic Aromatic Hydrocarbon (PAH) Deposition to Lake Sediments of Northwestern Canada - Desjardins, Cyndy (Université d'Ottawa / University of Ottawa, 2015)
With the rising demand for fossil fuels, Northern Canada has seen an unprecedented increase in petrochemical development. These developments are often associated with emissions of PAHs, a group of hydrophobic organic contaminants that are known to be carcinogenic and otherwise harmful to humans. Due to their hydrophobic nature, PAHs tend to bind to organic matter and can be produced through both anthropogenic and natural processes, making them ubiquitous in the environment. Therefore, in addition to impacts from petrochemical developments, changes to climatic conditions, such as increased forest fire disturbance and primary production also have the potential to alter delivery of organic carbon (OC) and PAHs to ecosystems. However, very little is known as to how the combined stressors of climate change and petrochemical development may affect environmental deposition of these contaminants. The concentrations and composition of parent and alkyl PAHs were analysed in radiometrically-dated sediment cores from lakes with one of four different types of petrochemical development in their catchments: (1) in-situ oil sands extraction (Cold Lake, AB); (2) open-pit oil sands extraction (Fort McMurray, AB); (3) abandoned conventional natural gas exploration (Mackenzie Delta Uplands, NWT); and (4) conventional gas and oil extraction (Cameron Hills, NWT). PAH deposition to lake sediments was also compared to climate reconstructions using climate proxies (diatom assemblages, inferred chlorophyll a and its diagenetic products, and Rock Eval carbon fractions as well as %OC). PAH sources were differentiated between potential pyrogenic and petrogenic origin over a period that extends to pre-industrial times using ratios of specific PAHs that can be traced to their potential source. Sediment cores from Cold Lake, AB showed concentrations of the sum of alkyl PAHs greater than those of parent PAHs, while all other cores show the reverse trend. A comparison of the % change of PAH concentrations from pre-development to post-development sediments between the four regions, showed that the greatest increase in concentrations of PAHs occurred in the Athabasca oil sands region. PAH profiles in the conventional regions have been historically dominated by mixed sources (pyrogenic PAHs from general background atmospheric inputs and petrogenic PAHs from the surrounding hydrocarbon-rich soils). While cores from the Fort McMurray area show a clear shift from pyrogenic sources (primarily wood and coal burning) in earlier sediments to petrogenic sources in more modern sediments, and the Cold Lake cores show some shifting sources to those dominated by pyrogenic sources in modern sediments. Organic carbon was significantly correlated with the sum of parent PAHs in 2 out of the 6 NWT cores that were examined for climate change impacts, while all other PAH parameters (concentration and composition) do not correlate significantly with any of the climate proxies. Establishing background concentrations and sources of PAHs in aquatic ecosystems is essential for understanding the natural environmental variations in these contaminants. Moreover, as both petrochemical activity and impacts from climate change are predicted to intensify in the future, studies such as this one allow us to build a solid understanding of how PAH deposition to northern lakes has responded to the warming climate and whether PAHs have been altered as a result of petrochemical activity.